2006
DOI: 10.1111/j.1468-2478.2006.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

The Politics of Shame: The Condemnation of Country Human Rights Practices in the UNCHR

Abstract: Although the United Nations Commission on Human Rights served as the primary forum in which governments publicly named and shamed others for abusing their citizens, the practices of the commission have been largely ignored by political scientists. To address that deficiency, this study analyzes the actions of the commission and its members' voting records in the 1977–2001 period. It establishes that targeting and punishment by the commission decreasingly fit the predictions of a realist perspective, in which n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
100
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(104 citation statements)
references
References 43 publications
1
100
1
2
Order By: Relevance
“…In practice, critics argue it is often akin to a dog that only barks little and bites even less. The same is said of the UN Human Rights Council (formerly UN Commission on Human Rights (UNCHR)), even if there is some evidence that it has become less partisan and politically motivated over time (Lebovic and Voeten 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, critics argue it is often akin to a dog that only barks little and bites even less. The same is said of the UN Human Rights Council (formerly UN Commission on Human Rights (UNCHR)), even if there is some evidence that it has become less partisan and politically motivated over time (Lebovic and Voeten 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Average marginal effects reported in table 4 indicate that autocracies which derogate from their ICCPR obligations are more likely to be targeted by the UN Commission on Human Rights over the period 1981 to 2000 (model 1) and also targeted by a stronger measure (model 2) ranging from discussion, to a confidential measure, advisory measure to a public resolution, using data taken from Lebovic and Voeten (2006). Note that this is despite controlling for the level of respect for human rights in these countries.…”
Section: Resultsmentioning
confidence: 99%
“…15. As discussed in the following chapters, recent scholarship on naming and shaming building on these arguments has focused more on the extent to which public criticism is correlated with changes in human rights behavior, often with conflicting results (e.g., Hafner-Burton 2008; Krain 2012; Lebovic and Voeten 2006;Murdie and Davis 2012;Ron, Ramos, and Rodgers 2005). 16.…”
Section: Notesmentioning
confidence: 97%
“…For example, Simmons (2000) analyzed states that were new entrants on the international scene, emerging from either a period of nondemocracy or global isolation and found that states were concerned with their reputations for respecting the rule of law because this affected the level of economic integration they were able to achieve. In addition, the power of shame which comes from a bad reputation has been found to be a strong deterrent for states, preventing them from engaging in norm-violating behavior (Donnelly 1998;Franklin 2008;Lebovic and Voeten 2006).…”
Section: A Theory Of Compliance and Reputationmentioning
confidence: 98%